Reducing Transport Intensity - Banister, David; Stead, Dominic (European Journal of Transport and Infrastructure Research, 2002)
In this paper, transport intensity concerns the economic or energy efficiency of transport. The focus of the paper is the measurement and use of indicators of transport intensity. Most research has concentrated on the volume and distance measures, which show continuous increases over time, normally at a rate that is higher than the growth in Gross Domestic Product (GDP). It is argued that an additional element needs to be included, namely transport efficiency, which relates to modes, technologies, organisational structures, the use of resources and prices. The measurement of GDP also needs to be extended. Measures of economic and transport energy efficiency are applied to EU countries and contrasted with similar measures for the USA and Canada. The empirical evidence is then placed in the wider context of globalisation and economic change, and the case for real decoupling is made for both the freight and passenger sectors.